Further glucosides of lichens' acids from Central Asian lichens - Rezanka, T; Guschina, I A (Phytochemistry, 2001)
Eight compounds isolated from an extract of Central Asian lichens comprised new glucosides having murolic, protoconstipatic and allo-murolic acids as the aglycones and a saccharide moiety linked at C-18 made up of four glucoses. The structures were elucidated using extensive spectroscopic analysis (1D and 2D NMR, MS, IR, UV and CD) and by chemical methods.
Keywords: lišejníky; Chromatography, High Pressure Liquid; glukosidy; Molecular Structure; Spectrometry, Mass, Fast Atom Bombardment; Glucosides; Lichens; Magnetic Resonance Spectroscopy; spektrometrie hmotnostní - bombardování rychlými atomy; magnetická rezonanční spektroskopie; vysokoúčinná kapalinová chromatografie; molekulární struktura